Effect of Drought Periods on Rice Lines Growth and Yield - Margaret, Swisci; Nafisah, Nafisah; Sujinah, Sujinah; Rumanti, Indrastuti Apri; Yunani, Nani (The University of Lampung, 2024)
Numerous variables, such as drought period, growth stage, and varieties, influence rice growth and yield in response to drought. This study was conducted to determine the effect of drought periods on the growth and yields of several rice lines and varieties as well as to select drought-tolerant lines. Using a split-plot design with three replications, the pot experiment was carried out in the greenhouse from December 2015 to April 2016 at the Sukamandi Experimental Site of Indonesian Center for Rice Research (BB Padi). Drought periods were treated as the main-plot, while the rice lines/varieties were treated as sub-plots. The main-plot consists of four levels: control, drought at the maximum tillering stage, drought at the primordia stage, and drought at the grain filling stage. The rice lines used are expand lines of rainfed lowland rice and upland rice from the BB Padi breeding program. The results showed that of the 36 rice lines and 6 varieties tested, drought periods during maximum tillering and primordia affected plant height, while the tiller number was not affected by all drought periods. From the yield characters, drought periods increased unfilled grain percentage and decreased 1000 grains weight and also grain weight per plant. Jatiluhur is consistently tolerant and has the highest yield. There are 8 rice lines with consistent tolerance and not significantly different yields with Jatiluhur: B13650E-TB-80-2, B14168E-MR-6, B14168E-MR-10, B14168E-MR-11, B14168E-MR-12, B14168E-MR-13, B12480D-MR-7-1-1, and B12056F-TB-1-29-1. Keywords: Drought periods, Rice lines, Growth, Yield